International Two-day Congress "Drug development & registration" Took Place in Moscow on February 2–3, 2023 - article Editorial (Разработка и регистрация лекарственных средств)
This year congress was devoted to the 10th anniversary of the "Drug development and registration magazine". We have changed and supplemented the program of the Congress in comparison with the events of previous years, and also added an online format. During the congress we have discussed such themes as drug development, non-clinical and clinical trials, drug production and registration.